A 0.002‐mm2 8‐bit 1‐MS/s low‐power time‐based DAC (T‐DAC) - Ali H. Hassan; Hassan Mostafa; Mohamed Refky; Khaled N. Salama; Ahmed M. Soliman (IET Circuits, Devices and Systems)
Abstract Digital‐to‐analogue converters (DACs) are essential blocks for interfacing the digital environment with the real world. A novel architecture, using a digital‐to‐time converter (DTC) and a time‐to‐voltage converter (TVC), is employed to form a low‐power time‐based DAC (T‐DAC) that fits low‐power low‐speed applications. This novel conversion mixes the digital input code into a digital pulse width modulated (D‐PWM) signal through the DTC circuit, then converts this D‐PWM signal into an analogue voltage through the TVC circuit. This new T‐DAC is not only an energy‐efficient design but also an area‐efficient implementation. Power optimization is achieved by controlling the supply voltage of the TVC circuit with a discontinuous waveform using a low bias current. Moreover, the implementation area is optimized by proposing a new DAC architecture with a coarse‐fine DTC circuit. Post‐layout simulations of the proposed T‐DAC is conducted using industrial hardware‐calibrated 0.13 μm. Complementary metal oxide semiconductor technology with a 1 V supply voltage, 1 MS/s conversion rate, and 0.9 μW power dissipation.